Taste Receptor Polymorphisms and Immune Response: A Review of Receptor Genotypic-Phenotypic Variations and Their Relevance to Chronic Rhinosinusitis - Triantafillou, Vasiliki; Workman, Alan D.; Kohanski, Michael A.; Cohen, Noam A. (Frontiers in Cellular and Infection Microbiology, 2018)
Bitter (T2R) and sweet taste (T1R) receptors have emerged as regulators of upper airway immune responses. Genetic variation of these taste receptors additionally confers susceptibility to infection and has been implicated in severity of disease in chronic rhinosinusitis (CRS). Ongoing taste receptor research has identified a variety of biologically active compounds that activate T1R and T2R receptors, increasing our understanding of not only additional receptor isoforms and their function but also how receptor function may contribute to the pathophysiology of CRS. This review will discuss the function of taste receptors in mediating airway immunity with a focus on recently described modulators of receptor function and directions for future research into the potential role of genotypic and phenotypic receptor variation as a predictor of airway disease and response to therapy.